Association of polycythemia vera with positive JAK2V617F mutation and myasthenia gravis: A report of two cases - Sreethish Sasi (14151873) (2023)
Screening for MG in patients with PV positive for JAK2V617F mutation can help in early diagnosis and treatment, resulting in a significant reduction in morbidity and mortality. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3574